Effect of material types on the fracture resistance of maxillary central incisors restored with CAD/CAM post and cores - Eid, Rita; Tribst, João Paulo Mendes [UNESP]; Juloski, Jelena; Ozcan, Multu; Salameh, Ziad (My University, 2021)
Aim: To evaluate the fracture resistance and failure pattern of endodontically treated teeth with post and cores made of different CAD/CAM materials in comparison with cast post and cores. Materials and methods: A total of 40 maxillary central incisors were divided into four groups. Post and cores were fabricated using the following materials: fiber-reinforced composite, high-density polymer, polymer-infiltrated ceramic network, and nonprecious metal alloy as a control group. Specimens were covered with lithium disilicate crowns and subjected to thermomechanical cyclic loading followed by fracture resistance testing until failure. One-way ANOVA followed by Bonferroni multiple comparison tests were used to determine significant differences between the four groups. The significance level was set at 0.05. 3D finite element analysis was then performed, and results were analyzed based on the von Mises stress distribution criteria and the maximum principal stress for the possible failure areas. Results: No statistically significant differences were found in the fracture resistance between the four groups. In terms of unrestorable failures, no significant differences were found among the tested groups. Conclusion:The tested post and cores have comparable fracture resistance to that of metallic cast post and cores in the anterior region. Clinical significance: Post and cores made of CAD/CAM materials offer an acceptable alternative for the restoration of anterior teeth.
Keywords: fiber-reinforced composite; finite element analysis; fracture resistance; hybrid ceramics; post and cores